EFFECTIVENESS OF AUGMENTED REALITY-BASED THERAPEUTIC PATIENT EDUCATION ON HEALTH LOCUS OF CONTROL IN TYPE 2 DIABETES MELLITUS PATIENTS - Fajriyah, Novita; Susanti; Kristiani, Rina Budi (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic disease with a rising global prevalence, significantly affecting patients' quality of life and the health system. Effective management of T2DM requires patients to actively regulate their diet, physical activity, and adherence to treatment. Health Locus of Control (HLC) measures the extent to which individuals believe their health is influenced by their actions (internal), others (powerful others), or chance. Augmented Reality (AR) technology presents an innovative method for therapeutic education, potentially enhancing patient engagement and learning effectiveness. Objectives: To analyze the effect of Augmented Reality-based therapeutic patient education on health locus of control in T2DM patients. Methods: A quasi-experimental design with pre- and post-tests and a control group was used. Non-probability purposive sampling selected 100 respondents, divided into an intervention group (50) and a control group (50). The Multidimensional Health Locus of Control questionnaire served as the research instrument. Univariate analysis described respondents' frequency distribution, mean, median, and standard deviation. Bivariate analysis utilized the Wilcoxon test. Results: Augmented Reality based Therapeutic Education significantly improved HLC scores in T2DM patients: Internal (p = 0.01), Powerful Others (p = 0.02), and Chance (p = 0.00). However, no significant difference was found between the intervention and control groups in terms of overall HLC improvement, indicating the need for further research to confirm these preliminary findings. Conclusion: Augmented Reality-based Therapeutic Education shows promise in enhancing patients' perception of control over their health. This innovative approach could significantly impact clinical practice and patient education.